Electromagnetic shielding foam and method of making and use thereof

CN118240284BActive Publication Date: 2026-10-20SHAANXI SCI TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410452075.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-15
Publication Date
2026-10-20
Estimated Expiration
2044-04-15

AI Technical Summary

Technical Problem

然而,上述电磁屏蔽材料的反射率>0.8,较高的反射率会致使大量电磁波在材料表面反射,未能被有效吸收,导致对环境的二次污染

Benefits of technology

[0026]本发明提供了上述技术方案所述电磁屏蔽泡沫的制备方法。本发明首先制备MXene@CoNi,将MXene和MXene@CoNi分别和纤维素纳米纤维进行复合,再通过逐层冷冻,使冷冻时水占据的位置形成空隙,制备得到电磁屏蔽泡沫,制备方法简单,成本低,绿色环保,适宜工业化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118240284B_ABST
    Figure CN118240284B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of electromagnetic shielding, and particularly relates to an electromagnetic shielding foam as well as a preparation method and application thereof. In the electromagnetic shielding foam provided by the application, the cellulose nanofiber layer has low conductivity, which is conducive to the incidence of electromagnetic waves into the electromagnetic shielding foam; the MXene@CoNi-cellulose nanofiber composite layer has moderate conductivity and magnetism, which can effectively absorb the electromagnetic waves entering the electromagnetic shielding foam and reduce the reflectivity; the MXene-cellulose nanofiber composite layer has high conductivity, and the electromagnetic waves are reflected to the MXene@CoNi-cellulose nanofiber composite layer for reabsorption; by setting a specific interlayer position relationship, the electromagnetic waves entering the electromagnetic shielding material can be effectively absorbed, the reflectivity is reduced, an excellent shielding effect is achieved, high electromagnetic loss and effective absorption of the electromagnetic waves are simultaneously realized, and secondary pollution of the electromagnetic waves is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electromagnetic shielding technology, specifically relating to an electromagnetic shielding foam, its preparation method, and its application. Background Technology

[0002] Electrical and electronic devices emit a large amount of electromagnetic waves during use, posing a significant threat to their normal and safe operation and the human living environment. Electromagnetic shielding materials are a new type of functional material that can effectively suppress electromagnetic wave pollution. They achieve electromagnetic shielding by blocking or attenuating the propagation of electromagnetic energy between the shielded area and the outside world. Traditional electromagnetic shielding materials are mainly conductive materials. By suppressing the propagation of electromagnetic waves, the waves cannot penetrate the material and instead enter the environment through reflection, thus achieving electromagnetic shielding and preventing interference and damage to electronic equipment and communication systems. Existing technology (Lei Wang, Zhonglei Ma, Hua Qiu, et al. Significantly Enhanced Electromagnetic Interference Shielding Performances of Epoxy Nanocomposites with Long-Range Aligned Lamellar Structures[J]. Nano-Micro Letters, 2022, 14: 224.) discloses an electromagnetic shielding material Ti3C2T. x @Fe3O4 / CNF exhibits excellent electromagnetic shielding performance. However, the reflectivity of this electromagnetic shielding material is >0.8. This high reflectivity causes a large number of electromagnetic waves to be reflected off the material surface and not effectively absorbed, leading to secondary pollution of the environment. Summary of the Invention

[0003] The purpose of this invention is to provide an electromagnetic shielding foam, its preparation method, and its application. The electromagnetic shielding foam provided by this invention has low reflectivity and can effectively absorb electromagnetic waves.

[0004] To achieve the above objectives, the present invention provides the following technical solution:

[0005] The present invention provides an electromagnetic shielding foam comprising sequentially stacked MXene-cellulose nanofiber composite layer, MXene@CoNi-cellulose nanofiber composite layer and cellulose nanofiber layer.

[0006] Preferably, by mass parts, it includes 7 to 67 parts of MXene@CoNi, 7 to 67 parts of MXene, and 3 to 75 parts of cellulose nanofibers.

[0007] Preferably, the thickness of the MXene-cellulose nanofiber composite layer is 0.1–10 mm; the MXene content in the MXene-cellulose nanofiber composite layer is 5–60 wt%.

[0008] The thickness of the MXene@CoNi-cellulose nanofiber composite layer is 0.1–10 mm; the content of MXene@CoNi in the MXene@CoNi-cellulose nanofiber composite layer is 5–60 wt%.

[0009] The thickness of the cellulose nanofiber layer is 0.1–10 mm.

[0010] This invention provides a method for preparing the electromagnetic shielding foam described in the above technical solution, comprising the following steps:

[0011] The first MXene and the first cellulose nanofiber aqueous dispersion were mixed to obtain the MXene dispersion;

[0012] A soluble cobalt salt, a soluble nickel salt, a lower alcohol, an alkaline earth metal hydroxide, a reducing agent, water, and a second MXene were mixed and subjected to a coprecipitation reaction to obtain MXene@CoNi.

[0013] The MXene@CoNi and the second cellulose nanofiber aqueous dispersion were mixed to obtain the MXene@CoNi dispersion;

[0014] The MXene dispersion, MXene@CoNi dispersion, and third cellulose nanofiber aqueous dispersion were frozen layer by layer to obtain electromagnetic shielding foam.

[0015] Preferably, the mass ratio of the second MXene to the soluble nickel salt is 1:1 to 4; the mass ratio of the second MXene to the soluble cobalt salt is 1:1 to 4.

[0016] Preferably, the temperature of the coprecipitation reaction is 30–200°C, and the time is 2–12 h.

[0017] Preferably, the lower alcohol includes ethanol, methanol, and propanol;

[0018] The alkaline earth metal hydroxides include sodium hydroxide and potassium hydroxide;

[0019] The reducing agent includes hydrazine hydrate.

[0020] Preferably, the solid-liquid ratio of the first MXene and the first cellulose nanofiber aqueous dispersion is 0.05-1g: 5-50mL;

[0021] The solid-liquid ratio of the MXene@CoNi and the second cellulose nanofiber aqueous dispersion is 0.05-1g: 5-50mL;

[0022] The mass percentage of cellulose nanofibers in the first, second, and third cellulose nanofiber aqueous dispersions is independently 0.1% to 5%.

[0023] Preferably, the temperature of the layer-by-layer freezing is -60 to -10°C, and the pressure is 1 to 30 Pa.

[0024] This invention provides the application of the electromagnetic shielding foam described in the above technical solution or the electromagnetic shielding foam prepared by the above technical solution in electronic packaging materials.

[0025] This invention provides an electromagnetic shielding foam, comprising sequentially stacked MXene-cellulose nanofiber composite layers, MXene@CoNi-cellulose nanofiber composite layers, and cellulose nanofiber layers. In the electromagnetic shielding foam provided by this invention, the cellulose nanofiber layer has low electrical conductivity, which is beneficial for electromagnetic waves to enter the interior of the electromagnetic shielding foam; the MXene@CoNi-cellulose nanofiber composite layer has moderate electrical conductivity and magnetism, which can effectively absorb electromagnetic waves entering the interior of the electromagnetic shielding foam and reduce reflectivity; the MXene-cellulose nanofiber composite layer has high electrical conductivity, so a large amount of electromagnetic waves are reflected back to the MXene@CoNi-cellulose nanofiber composite layer for further absorption. By setting a specific interlayer positional relationship, electromagnetic waves entering the electromagnetic shielding material can be effectively absorbed, achieving excellent shielding effect while reducing reflectivity, simultaneously realizing high electromagnetic loss and effective absorption of electromagnetic waves, and reducing secondary electromagnetic pollution. As shown in the test results of the embodiments, the electromagnetic shielding foam provided by this invention has a shielding effectiveness of 18–51 dB and a reflectivity of 0.21–0.59.

[0026] This invention provides a method for preparing the electromagnetic shielding foam described in the above technical solution. The invention first prepares MXene@CoNi, then composites MXene and MXene@CoNi with cellulose nanofibers, and then freezes layer by layer to create voids in the spaces occupied by water during freezing, thus obtaining the electromagnetic shielding foam. The preparation method is simple, low-cost, environmentally friendly, and suitable for industrial production. Attached Figure Description

[0027] Figure 1 A schematic diagram of the electromagnetic shielding foam provided by the present invention;

[0028] Figure 2 This is a schematic diagram of the structure of MXene@CoNi. Detailed Implementation

[0029] The present invention provides an electromagnetic shielding foam comprising sequentially stacked MXene-cellulose nanofiber composite layer, MXene@CoNi-cellulose nanofiber composite layer and cellulose nanofiber layer.

[0030] The electromagnetic shielding foam provided by the present invention preferably comprises 7 to 67 parts of MXene@CoNi, more preferably 10 to 60 parts, and most preferably 20 to 50 parts by weight. In the present invention, the MXene content in the MXene@CoNi-cellulose nanofiber composite layer is preferably 5 to 60 wt%, more preferably 10 to 50 wt%, and most preferably 20 to 30 wt%; the thickness of the MXene@CoNi-cellulose nanofiber composite layer is preferably 0.1 to 10 mm, more preferably 1 to 8 mm, and most preferably 3 to 5 mm.

[0031] Based on the mass fraction of MXene@CoNi, the electromagnetic shielding foam provided by this invention preferably comprises 7 to 67 parts of MXene, more preferably 10 to 60 parts, and most preferably 20 to 50 parts. In this invention, the MXene content in the MXene-cellulose nanofiber composite layer is preferably 5 to 60 wt%, more preferably 10 to 50 wt%, and most preferably 20 to 30 wt%; the thickness of the MXene-cellulose nanofiber composite layer is preferably 0.1 to 10 mm, more preferably 1 to 8 mm, and most preferably 3 to 5 mm.

[0032] Based on the mass fraction of MXene@CoNi, the electromagnetic shielding foam provided by this invention preferably comprises 3 to 75 parts of cellulose nanofibers, more preferably 10 to 70 parts, and most preferably 30 to 50 parts. In this invention, the thickness of the cellulose nanofiber composite layer is preferably 0.1 to 10 mm, more preferably 1 to 8 mm, and most preferably 3 to 5 mm.

[0033] This invention provides a method for preparing the electromagnetic shielding foam described in the above technical solution, comprising the following steps:

[0034] The first MXene and the first cellulose nanofiber aqueous dispersion were mixed to obtain the MXene dispersion;

[0035] A soluble cobalt salt, a soluble nickel salt, a lower alcohol, an alkaline earth metal hydroxide, a reducing agent, water, and a second MXene were mixed and subjected to a coprecipitation reaction to obtain MXene@CoNi.

[0036] The MXene@CoNi and the second cellulose nanofiber aqueous dispersion were mixed to obtain the MXene@CoNi dispersion;

[0037] The MXene dispersion, MXene@CoNi dispersion, and third cellulose nanofiber aqueous dispersion were frozen layer by layer to obtain electromagnetic shielding foam.

[0038] Unless otherwise specified, the materials and equipment used in this invention are all commercially available products in the field.

[0039] The source of MXene will be explained in detail below.

[0040] In this invention, the MXene is preferably a commercially available product or prepared in-house. The preparation method of the MXene preferably includes the following steps: mixing titanium aluminum carbide and an etchant, performing aluminum etching, and then stripping to obtain the MXene.

[0041] In this invention, the etchant preferably comprises hydrofluoric acid or a lithium fluoride-hydrochloric acid solution. In this invention, when the etchant is a lithium fluoride-hydrochloric acid solution, the mass ratio of the titanium aluminum carbide to the lithium fluoride in the lithium fluoride-hydrochloric acid solution is preferably 1:0.5–5, more preferably 1:1–4, and most preferably 1:2–3.

[0042] In this invention, the preparation method of the lithium fluoride-hydrochloric acid solution preferably includes the following steps: mixing lithium fluoride and hydrochloric acid to obtain the lithium fluoride-hydrochloric acid solution. In this invention, the solid-liquid ratio of lithium fluoride and hydrochloric acid is preferably 1-12 g: 8-110 mL, more preferably 8-11 g: 20-100 mL, and most preferably 9-10 g: 50-90 mL; the concentration of the hydrochloric acid is preferably 1-10 M (mol / L), more preferably 2-9 M, and most preferably 6-8 M. This invention does not specifically limit the mixing method; any mixing method well known in the art can be used, such as ultrasonic mixing. In this invention, the ultrasonic mixing time is preferably 3-30 min, more preferably 5-20 min, and most preferably 10-15 min.

[0043] In this invention, the preferred method for mixing titanium aluminum carbide and the etchant is ice bath mixing.

[0044] In this invention, the etching temperature of aluminum is preferably 15-65°C, more preferably 20-60°C, and most preferably 30-40°C; the etching time of aluminum is preferably 12-36h, more preferably 18-30h, and most preferably 24-28h.

[0045] After the aluminum etching is completed, the present invention preferably further includes: washing the multilayer MXene obtained by the aluminum etching with water until neutral, and stripping the resulting supernatant. In the present invention, the stripping preferably includes ultrasonic stripping; the ultrasonic power of the ultrasonic stripping is preferably 10-900W, more preferably 50-800W, and most preferably 100-700W; the ultrasonic stripping time is preferably 2-100min, more preferably 20-90min, and most preferably 50-80min.

[0046] After the stripping is completed, the present invention preferably further includes: performing solid-liquid separation on the stripped system obtained by the stripping, and drying the resulting solid component. The present invention does not specifically limit the method of solid-liquid separation; any solid-liquid separation method well known in the art can be used, such as one or more of centrifugation, filtration, and vacuum filtration. In the present invention, the centrifugation time is preferably 30–120 min, more preferably 50–100 min, and most preferably 60–90 min. In the present invention, the drying is preferably freeze-drying. In the present invention, the freeze-drying temperature is preferably -80–-5°C, more preferably -60–-10°C, and most preferably -40–-20°C; the freeze-drying pressure is preferably 1–200 Pa, more preferably 10–100 Pa, and most preferably 20–50 Pa.

[0047] The present invention mixes a first MXene and a first cellulose nanofiber aqueous dispersion to obtain an MXene dispersion.

[0048] In this invention, the solid-liquid ratio of the first MXene and the first cellulose nanofiber aqueous dispersion is preferably 0.05-1g:5-50mL, more preferably 0.1-0.8g:10-40mL, and most preferably 0.3-0.5g:20-30mL; the mass percentage of cellulose nanofibers in the first cellulose nanofiber aqueous dispersion is preferably 0.1-5%, more preferably 0.5-1%, and most preferably 0.8-1%.

[0049] This invention involves mixing soluble cobalt salt, soluble nickel salt, lower alcohol, alkaline earth metal hydroxide, reducing agent, water, and second MXene, and then performing a co-precipitation reaction to obtain MXene@CoNi.

[0050] In this invention, the lower alcohol preferably includes ethanol, methanol, propanol, and more preferably ethanol; the solid-liquid ratio of the second MXene and the lower alcohol is preferably 1g:1-50mL, more preferably 1g:10-40mL, and most preferably 1g:20-30mL.

[0051] In this invention, the alkaline earth metal hydroxide preferably includes sodium hydroxide and potassium hydroxide, more preferably sodium hydroxide; the alkaline earth metal hydroxide is preferably used in the form of an aqueous solution. In this invention, the concentration of the aqueous solution is preferably 1–13 M, more preferably 2–12 M, and most preferably 5–10 M; the solid-liquid ratio of the second MXene to the aqueous solution is preferably 1 g: 10–50 mL, more preferably 1 g: 20–40 mL, and most preferably 1 g: 30–35 mL.

[0052] In this invention, the reducing agent preferably includes hydrazine hydrate; the solid-liquid ratio of the second MXene and the reducing agent is preferably 1g:10-50mL, more preferably 1g:20-40mL, and most preferably 1g:30-35mL.

[0053] This invention does not specifically limit the soluble cobalt salt used; any soluble cobalt salt well known to those skilled in the art can be used, such as cobalt chloride and / or cobalt nitrate. In this invention, the mass ratio of the second MXene to the soluble cobalt salt is preferably 1:1 to 4, more preferably 1:1 to 3, and most preferably 1:2 to 3.

[0054] The present invention does not have any particular limitation on the soluble nickel salt, and any soluble nickel salt well known to those skilled in the art can be used, such as nickel chloride and / or nickel nitrate; the mass ratio of the second MXene to the soluble nickel salt is preferably 1:1 to 4, more preferably 1:1 to 3, and most preferably 1:2 to 3.

[0055] In this invention, the solid-liquid ratio of the second MXene to water is preferably 1g:10-50mL, more preferably 1g:20-40mL, and most preferably 1g:30-35mL.

[0056] In this invention, the mixing of the soluble cobalt salt, soluble nickel salt, lower alcohol, alkaline earth metal hydroxide, reducing agent, water, and second MXene preferably includes: first mixing the soluble cobalt salt, soluble nickel salt, lower alcohol, water, and second MXene to obtain a pre-reaction solution; and second mixing the pre-reaction solution, alkaline earth metal hydroxide, and reducing agent. This invention does not specifically limit the method of the first mixing; any mixing method well-known in the art can be used, such as ultrasonic mixing. In this invention, the first mixing time is preferably 1–10 min, more preferably 2–8 min, and most preferably 3–7 min.

[0057] In this invention, the temperature of the coprecipitation reaction is preferably 30-200℃, more preferably 50-180℃, and most preferably 80-150℃; the time of the coprecipitation reaction is preferably 2-12h, more preferably 3-10h, and most preferably 5-7h.

[0058] After obtaining MXene@CoNi, the present invention mixes the MXene@CoNi with the second cellulose nanofiber aqueous dispersion to obtain an MXene@CoNi dispersion.

[0059] In this invention, the solid-liquid ratio of the MXene@CoNi and the second cellulose nanofiber aqueous dispersion is preferably 0.05-1g:5-50mL, more preferably 0.1-0.8g:10-40mL, and most preferably 0.3-0.5g:20-30mL; the mass percentage of cellulose nanofibers in the second cellulose nanofiber aqueous dispersion is preferably 0.1-5%, more preferably 0.5-1%, and most preferably 0.8-1%.

[0060] After obtaining MXene dispersion and MXene@CoNi dispersion, the present invention freezes the MXene dispersion, MXene@CoNi dispersion and third cellulose nanofiber aqueous dispersion layer by layer to obtain electromagnetic shielding foam.

[0061] In this invention, the mass percentage of cellulose nanofibers in the third cellulose nanofiber aqueous dispersion is preferably 0.1-5%, more preferably 0.5-1%, and most preferably 0.8-1%.

[0062] In this invention, the temperature of the layer-by-layer freezing is preferably -60 to -10°C, more preferably -50 to -20°C, and most preferably -40 to -30°C; the pressure of the layer-by-layer freezing is preferably 1 to 30 Pa, more preferably 5 to 20 Pa, and most preferably 10 to 15 Pa.

[0063] In this invention, prior to the layer-by-layer freezing, it is preferable to further pre-freeze the MXene dispersion, MXene@CoNi dispersion, and third cellulose nanofiber aqueous dispersion, respectively. In this invention, the pre-freezing temperature is preferably -273 to -90°C, more preferably -160 to -100°C, and most preferably -140 to -120°C.

[0064] This invention provides the application of the electromagnetic shielding foam described in the above technical solution or the electromagnetic shielding foam prepared by the above technical solution in electronic packaging materials.

[0065] To further illustrate the present invention, the following detailed description, in conjunction with the accompanying drawings and embodiments, provides an electromagnetic shielding foam, its preparation method, and its application, but these descriptions should not be construed as limiting the scope of protection of the present invention.

[0066] Example 1

[0067] Figure 1The schematic diagram shows the electromagnetic shielding foam provided by this invention. The specific preparation method is as follows:

[0068] 10 g of LiF was added to 100 mL of 6 M HCl aqueous solution, and the mixture was ultrasonically mixed for 15 min. Then, 6 g of Ti3AlC2 was added (completely added within 20 min) under an ice bath at 0 °C. Aluminum etching was performed at 65 °C for 24 h to obtain multilayer MXene. The multilayer MXene was washed with deionized water until the solution pH was neutral. Then, the multilayer MXene was dispersed in deionized water and centrifuged to wash away unetched Ti3AlC2. The supernatant was then ultrasonically exfoliated using a cell disruptor under inert gas protection and an ice bath (ultrasonic power 200 W, time 5 min). The exfoliated product was centrifuged for 40 min. The supernatant was filtered and freeze-dried to obtain MXene (sparse layer).

[0069] 3g CoCl2, 3g NiCl2, 0.3g MXene, and 30mL ethanol were added to 30mL deionized water and ultrasonically mixed for 10min. Then, 30mL of 12M sodium hydroxide aqueous solution and 30mL of hydrazine hydrate were added, and the mixture was reacted at 160℃ for 10h to obtain MXene@CoNi. Its structural schematic diagram is shown below. Figure 2 As shown.

[0070] 0.05 g MXene was dispersed in 10 mL of a 1% (w / w) aqueous dispersion of cellulose nanofibers to obtain an MXene dispersion; 0.05 g MXene@CoNi was dispersed in 10 mL of a 1% (w / w) aqueous dispersion of cellulose nanofibers to obtain an MXene@CoNi dispersion; the obtained MXene dispersion, MXene@CoNi dispersion, and cellulose nanofiber aqueous dispersion (10 mL, 1% (w / w)) were sequentially added to a mold, frozen at -100℃, and then freeze-dried at 10 Pa and -60℃ to obtain electromagnetic shielding foam. The shielding effectiveness of the prepared electromagnetic shielding foam was tested to be 18 dB, and the reflectivity was 0.13.

[0071] Example 2

[0072] Add 9g of LiF to 90mL of 7M HCl aqueous solution, sonicate for 15min, then add 8g of Ti3AlC2 (completely added within 20min) under an ice bath at 0℃. Etch aluminum at 65℃ for 24h to obtain multilayer MXene. Wash the multilayer MXene with deionized water until the solution pH is neutral, then disperse the multilayer MXene in deionized water and centrifuge to remove unetched Ti3AlC2. Take the supernatant and sonicate it under inert gas protection and an ice bath using a cell disruptor (ultrasonic power 300W, time 10min). Centrifuge the exfoliated product for 50min. Filter the supernatant and freeze-dry to obtain MXene (sparse layer).

[0073] 4g CoCl2, 3g NiCl2, 0.2g MXene, and 30mL ethanol were added to 30mL deionized water and ultrasonically mixed for 10min. Then, 30mL of 11M sodium hydroxide aqueous solution and 30mL of hydrazine hydrate were added, and the mixture was reacted at 160℃ for 10h to obtain MXene@CoNi.

[0074] 0.3 g of MXene was dispersed in 10 mL of a 0.8% (w / w) aqueous dispersion of cellulose nanofibers to obtain an MXene dispersion; 0.3 g of MXene@CoNi was dispersed in 10 mL of a 0.8% (w / w) aqueous dispersion of cellulose nanofibers to obtain an MXene@CoNi dispersion; the obtained MXene dispersion, MXene@CoNi dispersion, and 10 mL of a 0.8% (w / w) aqueous dispersion of cellulose nanofibers were sequentially added to a mold, frozen at -120℃, and then freeze-dried at 20 Pa and -60℃ to obtain electromagnetic shielding foam. The shielding effectiveness of the prepared electromagnetic shielding foam was tested to be 45 dB, and the reflectivity was 0.21.

[0075] Example 3

[0076] 7 g of LiF was added to 95 mL of 8 M HCl aqueous solution, and the mixture was ultrasonically mixed for 15 min. Then, 7 g of Ti3AlC2 was added (completely added within 20 min) under an ice bath at 0 °C. Aluminum etching was performed at 65 °C for 24 h to obtain multilayer MXene. The multilayer MXene was washed with deionized water until the solution pH was neutral. Then, the multilayer MXene was dispersed in deionized water and centrifuged to wash away unetched Ti3AlC2. The supernatant was then ultrasonically exfoliated using a cell disruptor under inert gas protection and an ice bath (ultrasonic power 400 W, time 6 min). The exfoliated product was centrifuged for 50 min. The supernatant was filtered and freeze-dried to obtain MXene (sparse layer).

[0077] Add 3g CoCl2, 2g NiCl2, 0.4g MXene, and 30mL ethanol to 30mL deionized water, sonicate for 10min, then add 30mL of 12.5M sodium hydroxide aqueous solution and 30mL of hydrazine hydrate, and react at 160℃ for 10h to obtain MXene@CoNi.

[0078] 0.3 g of MXene was dispersed in 20 mL of a 1% (w / w) aqueous dispersion of cellulose nanofibers to obtain an MXene dispersion; 0.4 g of MXene@CoNi was dispersed in 20 mL of a 1% (w / w) aqueous dispersion of cellulose nanofibers to obtain an MXene@CoNi dispersion; the obtained MXene dispersion, MXene@CoNi dispersion, and cellulose nanofiber aqueous dispersion (20 mL, 1% (w / w)) were sequentially added to a mold, frozen at -160℃, and then freeze-dried at 7 Pa and -60℃ to obtain electromagnetic shielding foam. The shielding effectiveness of the prepared electromagnetic shielding foam was tested to be 29 dB, and the reflectivity was 0.29.

[0079] Example 4

[0080] 9.5 g of LiF was added to 90 mL of 9M HCl aqueous solution and ultrasonically mixed for 15 min. Then, 6 g of Ti3AlC2 was added (completely added within 20 min) under an ice bath at 0 °C. Aluminum etching was performed at 65 °C for 24 h to obtain multilayer MXene. The multilayer MXene was washed with deionized water until the solution pH was neutral. Then, the multilayer MXene was dispersed in deionized water and centrifuged to wash away unetched Ti3AlC2. The supernatant was then ultrasonically exfoliated using a cell disruptor under inert gas protection and an ice bath (ultrasonic power 300 W, time 10 min). The exfoliated product was centrifuged for 30 min. The supernatant was filtered and freeze-dried to obtain MXene (sparse layer).

[0081] Add 3g CoCl2, 2g NiCl2, 0.6g MXene, and 30mL ethanol to 30mL deionized water, sonicate for 10min, then add 30mL of 10M sodium hydroxide aqueous solution and 30mL of hydrazine hydrate, and react at 160℃ for 10h to obtain MXene@CoNi.

[0082] 0.4 g of MXene was dispersed in 20 mL of a 0.5% (w / w) aqueous dispersion of cellulose nanofibers to obtain an MXene dispersion; 0.3 g of MXene@CoNi was dispersed in 20 mL of a 0.5% (w / w) aqueous dispersion of cellulose nanofibers to obtain an MXene@CoNi dispersion; the obtained MXene dispersion, MXene@CoNi dispersion, and cellulose nanofiber aqueous dispersion (20 mL, 0.5% (w / w)) were sequentially added to a mold, frozen at -140℃, and then freeze-dried at 4 Pa ​​and -60℃ to obtain electromagnetic shielding foam. The shielding effectiveness of the prepared electromagnetic shielding foam was tested to be 38 dB, and the reflectivity was 0.33.

[0083] Example 5

[0084] 9 g of LiF was added to 110 mL of 7 M HCl aqueous solution, and the mixture was ultrasonically mixed for 15 min. Then, 7 g of Ti3AlC2 was added (completely added within 20 min) under an ice bath at 0 °C. Aluminum etching was performed at 65 °C for 24 h to obtain multilayer MXene. The multilayer MXene was washed with deionized water until the solution pH was neutral. Then, the multilayer MXene was dispersed in deionized water and centrifuged to wash away unetched Ti3AlC2. The supernatant was then ultrasonically exfoliated using a cell disruptor under inert gas protection and an ice bath (ultrasonic power 200 W, time 9 min). The exfoliated product was centrifuged for 40 min. The supernatant was filtered and freeze-dried to obtain MXene (sparse layer).

[0085] Add 3g CoCl2, 4g NiCl2, 0.5g MXene, and 30mL ethanol to 30mL deionized water, sonicate for 10min, then add 30mL of 12M sodium hydroxide aqueous solution and 30mL of hydrazine hydrate, and react at 160℃ for 10h to obtain MXene@CoNi.

[0086] 0.4 g of MXene was dispersed in 15 mL of a 0.3% (w / w) aqueous dispersion of cellulose nanofibers to obtain an MXene dispersion; 0.4 g of MXene@CoNi was dispersed in 15 mL of a 0.3% (w / w) aqueous dispersion of cellulose nanofibers to obtain an MXene@CoNi dispersion; the obtained MXene dispersion, MXene@CoNi dispersion, and cellulose nanofiber aqueous dispersion (15 mL, 0.3% (w / w)) were sequentially added to a mold, frozen at -120℃, and then freeze-dried at 8 Pa and -60℃ to obtain electromagnetic shielding foam. The shielding effectiveness of the prepared electromagnetic shielding foam was tested to be 51 dB, and the reflectivity was 0.59.

[0087] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative intent, and these embodiments all fall within the protection scope of the present invention.

Claims

1. An electromagnetic shielding foam, characterized in that, It includes sequentially stacked MXene-cellulose nanofiber composite layers, MXene@CoNi-cellulose nanofiber composite layers, and cellulose nanofiber layers; The method for preparing the electromagnetic shielding foam includes the following steps: The first MXene and the first cellulose nanofiber aqueous dispersion were mixed to obtain the MXene dispersion; A soluble cobalt salt, a soluble nickel salt, a lower alcohol, an alkaline earth metal hydroxide, a reducing agent, water, and a second MXene were mixed and subjected to a coprecipitation reaction to obtain MXene@CoNi. The MXene@CoNi and the second cellulose nanofiber aqueous dispersion were mixed to obtain the MXene@CoNi dispersion; The MXene dispersion, MXene@CoNi dispersion, and third cellulose nanofiber aqueous dispersion were frozen layer by layer to obtain electromagnetic shielding foam. The preparation method of MXene includes the following steps: mixing titanium aluminum carbide and an etchant, performing aluminum etching, and then peeling off to obtain MXene.

2. The electromagnetic shielding foam according to claim 1, characterized in that, By weight, it includes 7-67 parts of MXene@CoNi, 7-67 parts of MXene, and 3-75 parts of cellulose nanofibers.

3. The electromagnetic shielding foam according to claim 1 or 2, characterized in that, The thickness of the MXene-cellulose nanofiber composite layer is 0.1~10 mm; the MXene content in the MXene-cellulose nanofiber composite layer is 5~60 wt%. The thickness of the MXene@CoNi-cellulose nanofiber composite layer is 0.1~10mm; the content of MXene@CoNi in the MXene@CoNi-cellulose nanofiber composite layer is 5~60wt%; The thickness of the cellulose nanofiber layer is 0.1~10 mm.

4. The method for preparing the electromagnetic shielding foam according to any one of claims 1 to 3, characterized in that, Includes the following steps: The first MXene and the first cellulose nanofiber aqueous dispersion were mixed to obtain the MXene dispersion; A soluble cobalt salt, a soluble nickel salt, a lower alcohol, an alkaline earth metal hydroxide, a reducing agent, water, and a second MXene were mixed and subjected to a coprecipitation reaction to obtain MXene@CoNi. The MXene@CoNi and the second cellulose nanofiber aqueous dispersion were mixed to obtain the MXene@CoNi dispersion; The MXene dispersion, MXene@CoNi dispersion, and third cellulose nanofiber aqueous dispersion were frozen layer by layer to obtain electromagnetic shielding foam. The preparation method of MXene includes the following steps: mixing titanium aluminum carbide and an etchant, performing aluminum etching, and then peeling off to obtain MXene.

5. The preparation method according to claim 4, characterized in that, The mass ratio of the second MXene to the soluble nickel salt is 1:1~4; The mass ratio of the second MXene to the soluble cobalt salt is 1:1~4.

6. The preparation method according to claim 4 or 5, characterized in that, The coprecipitation reaction is carried out at a temperature of 30~200℃ for 2~12 hours.

7. The preparation method according to claim 4, characterized in that, The lower alcohols include ethanol, methanol, and propanol; The alkaline earth metal hydroxides include sodium hydroxide and potassium hydroxide; The reducing agent includes hydrazine hydrate.

8. The preparation method according to claim 4, characterized in that, The solid-liquid ratio of the first MXene and the first cellulose nanofiber aqueous dispersion is 0.05~1g:5~50mL; The solid-liquid ratio of the MXene@CoNi and the second cellulose nanofiber aqueous dispersion is 0.05~1g:5~50mL; The mass percentage of cellulose nanofibers in the first, second, and third cellulose nanofiber aqueous dispersions is independently 0.1% to 5%.

9. The preparation method according to claim 4 or 8, characterized in that, The temperature for the layer-by-layer freezing is -60 to -10°C, and the pressure is 1 to 30 Pa.

10. The application of the electromagnetic shielding foam according to any one of claims 1 to 3 or the electromagnetic shielding foam prepared by the preparation method according to any one of claims 4 to 9 in electronic packaging materials.